Development of Cu-SiC composite for electrical discharge machining electrode using powder metallurgy technique - Ahmad Razi, Fatimah Azreen; Sutjipto, Agus Geter Edy; Mohamad, Souad A. (Trans Tech Publications, 2012)
In this research, composites containing 10-50 vol% SiC whiskers reinforced Cu matrix were fabricated using powder metallurgy technique. The mixtures were blended in a ball milling machine with the addition of ethanol for 2 hours at 150 rpm. The mixtures were allowed to dry in an oven at temperature of 40 °C. Then, the mixtures were uniaxially compacted into a cylindrical pallet of Φ 13.5 x 2 mm under compaction pressure of 472 MPa. It was followed by sintering in vacuum furnace at temperatures of 800-950 °C for 4 hours. The density, microhardness, electrical resistivity, thermal conductivity and microscopy analysis of the sintered composites were studied and reported in this paper.